Fitness Level and Not Aging per se, Determines the Oxygen Uptake Kinetics Response - George, Mitchell A.; McLay, Kaitlin M.; Doyle-Baker, Patricia K.; Reimer, Raylene A.; Murias, Juan M. (Frontiers in Physiology, 2018)
Although aging has been associated to slower V˙O2 kinetics, some evidence indicates that fitness status and not aging per se might modulate this response. The main goal of this study was to examine the V˙O2, deoxygenated hemoglobin+myoglobin (deoxy-[Hb+Mb]) kinetics, and the NIRS-derived vascular reperfusion responses in older compared to young men of different training levels (i.e., inactive, recreationally active, and endurance trained). Ten young inactive [YI; 26 ± 5 yrs.; peak V˙O2 (V˙O2peak), 2.96 ± 0.55 L·min−1], 10 young recreationally active (YR; 26 ± 6 yrs.; 3.92 ± 0.33 L·min−1), 10 young endurance trained (YT; 30 ± 4 yrs.; 4.42 ± 0.32 L·min−1), 7 older inactive (OI; 69 ± 4 yrs.; 2.50 ± 0.31 L·min−1), 10 older recreationally active (OR; 69 ± 5 yrs.; 2.71 ± 0.42 L·min−1), and 10 older endurance trained (OT; 66 ± 3 yrs.; 3.20 ± 0.35 L·min−1) men completed transitions of moderate intensity cycling exercise (MODS) to determine V˙O2 and deoxy-[Hb+Mb] kinetics, and the deoxy-[Hb+Mb]/V˙O2 ratio. The time constant of V˙O2 (τV˙O2) was greater in YI (38.8 ± 10.4 s) and OI (44.1 ± 10.8 s) compared with YR (26.8 ± 7.5 s) and OR (26.6 ± 6.5 s), as well as compared to YT (14.8 ± 3.4 s), and OT (17.7 ± 2.7 s) (p < 0.05). τV˙O2 was greater in YR and OR compared with YT and OT (p < 0.05). The deoxy-[Hb+Mb]/V˙O2 ratio was greater in YI (1.23 ± 0.05) and OI (1.29 ± 0.08) compared with YR (1.11 ± 0.03) and OR (1.13 ± 0.06), as well as compared to YT (1.01 ± 0.03), and OT (1.06 ± 0.03) (p < 0.05). Similarly, the deoxy-[Hb+Mb]/ V˙O2 ratio was greater in YR and OR compared with YT and OT (p < 0.05). There was a main effect of training (p = 0.033), whereby inactive (p = 0.018) and recreationally active men (p = 0.031) had significantly poorer vascular reperfusion than endurance trained men regardless of age. This study demonstrated not only that age-related slowing of V˙O2 kinetics can be eliminated in endurance trained individuals, but also that inactive lifestyle negatively impacts the V˙O2 kinetics response of young healthy individuals.